2016
DOI: 10.1088/1367-2630/18/12/125002
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual design of the beam source for the DEMO Neutral Beam Injectors

Abstract: DEMO (DEMOnstration Fusion Power Plant) is a proposed nuclear fusion power plant that is intended to follow the ITER experimental reactor. The main goal of DEMO will be to demonstrate the possibility to produce electric energy from the fusion reaction. The injection of high energy neutral beams is one of the main tools to heat the plasma up to fusion conditions. A conceptual design of the Neutral Beam Injector (NBI) for the DEMO fusion reactor, is currently being developed by Consorzio RFX in collaboration wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Within EUROfusion, the 'European Consortium for the Development of Fusion Energy', a conceptual design of the beam source for DEMO is being developed [3,25] in the Work Package Heating and Current Drive (WPHCD) under the Power Plant Physics and Technology (PPPT) activities to fulfill in the best way the requirements on a neutral beam injector for the DEMO fusion reactor [26]. The requirements placed on the ion source are close to the ones for ITER.…”
Section: Relevance For Demo Nbi Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within EUROfusion, the 'European Consortium for the Development of Fusion Energy', a conceptual design of the beam source for DEMO is being developed [3,25] in the Work Package Heating and Current Drive (WPHCD) under the Power Plant Physics and Technology (PPPT) activities to fulfill in the best way the requirements on a neutral beam injector for the DEMO fusion reactor [26]. The requirements placed on the ion source are close to the ones for ITER.…”
Section: Relevance For Demo Nbi Systemsmentioning
confidence: 99%
“…The requirements placed on the ion source are close to the ones for ITER. In principle, the source module is based on the modular RF source concept whereas the route of having a large expansion chamber powered by multiple drivers is followed as well as the route of having individual smaller sources (up to 20) [25]. Besides the RAMI issues which need to be fulfilled by all components of the machine, specific R&D topics for the ion source have been identified as well [27] and are part of the WPHCD R&D work programme.…”
Section: Relevance For Demo Nbi Systemsmentioning
confidence: 99%
“…In the following sections of this chapter, each of the aforementioned aspects is discussed more in detail and some suggestions given as to how problems arising from each aspect may be resolved and the parameters of the future injectors achieved. However it is important to understand that although various basic conceptual designs of an injector to be used on a fusion reactor have been considered [1][2][3], no concept has been chosen, and no serious engineering design of any concept has been carried out. Experience with the design of the neutral beam systems has shown that many aspects of the conceptual design are changed significantly during the engineering design phase.…”
Section: Basic Considerations For a Neutral Beam Injection System On mentioning
confidence: 99%
“…The future of fusion power requires a major step to establish the relevant economical and energetic efficiencies and feasibility. The conceptual design of the NBI of the DEMOnstration fusion power plant (DEMO) developed within the heating and current drive work package of EUROfusion [34] is introduced [35]. An example on the activities on smaller test facilities is given by McAdams et al (Culham Centre for Fusion Energy), in which an RF-driven volume source is used to systematically investigate the limits of neutralization and energy recovery.…”
Section: Negative Ion Source Beam Intensities Across 20 Orders Of Magmentioning
confidence: 99%